PROSES AFIKSASI CRIKAK “DUDU RAMA LAN SHINTA” KARYA SURYADI WS. SEBAGAI PEMAHAMAN MAKNA KATA BERBAHASA JAWA - Asri, Ella Purwita; Addila, Jasmine Findy; Aprillia, Jenny (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
THE AFFIXATION PROCESS IN CRIKAK 'DUDU RAMA LAN SHINTA' BY SURYADI WS. AS AN UNDERSTANDING OF JAVANESE WORD MEANINGSStudying affixations has become a common thing for literature enthusiasts. This research examines affixations in the crikak text entitled "Dudu Rama lan Shinta" by Suryadi WS. In the Panjebar Semangat media, Javanese short stories are a genre in modern Javanese literature. This research aims to examine affixation and understand the meaning of Javanese words. The method used in this research is library research using a qualitative descriptive approach, document analysis by repeatedly reading sentences and taking notes and making a list of words that have undergone a morphological process. This research data is in the form of written data with affixed words and the research data source is documents in the form of crikak from the Panjebar Semangat magazine. The results of the research show that the affixations found in the crikak of the Panjebar Semangat magazine are: {1} 6 ater-ater (prefix), {2} 5 seselan (infix), {3} 7 panambang (suffix), {4} 9 affixes together (confix) which consists of 3 affixes together in a row and 6 affixes in a row. From the results of this research, it can be found that the concurrent affix (confix) has the most data, namely 9 data including {ka- + -an}, {pa- + -an}, {ke- + -an}, {ng- + - i}, {ng- + - ake}, {di- + -i}, {di- + -ake}, {dak- + -ake} and {sa- + -e}.